Studi Perkiraan Pembentukan Indeks Scale Brine Sintetik Air Formasi (Variabel CO3 dalam Air Formasi) - Astuti, Dian Indri; Sri Rahayu Gusmawarni; M Sri Prasetyo Budi (Institut Teknologi Nasional Yogyakarta, 2024)
Decrease in oil production that occurs due to the presence of solids in production equipment caused by ion imbalances in formation water.due to ion imbalance in formation water. Scale formation can be influenced by several factors including the property characteristics property characteristics of the produced fluid, especially in heavy oil types, due to changes in temperature, pressure, pH, and mineral composition of formation water that exceeds the solubility limit. solubility triggers the formation of scale solids. In oil wells will usually formation water containing ions of calcium, barium, carbonate, sulphate, magnesium, sodium and chloride. In this study, the manufacture of synthetic brine with a composition that resembles field formation water as an alternative in laboratory scale scale index measurement testing solutions and and save time so as to speed up testing. Manufacture of synthetic brine this synthetic brine can utilise materials from the laboratory such as calcium, barium, carbonate, sulphate, magnesium, sodium and chloride dissolved in distilled water. Then experiments were carried out to change the mass of one or in the formation water formula on several mineral ions as a key in making synthetic brine.key in making synthetic brine that resembles the conditions in the field. Brine testing using the compleximetric method of formation water analysis chemically and physically like testing formation water from the field.